Dansk Mission i Sydindien 1918-1939 - Bugge, K. E. (Kirkehistoriske Samlinger, 1993)
This article reviews the doctoral thesis written by Bent Smidt Hansen: »Afhængighed og identitet. Kulturmødeproblemer i forbindelse med dansk mission i Sydindien i tiden mellem de to verdenskrige«13 Publisher: Aarhus Universitetsforlag, 1992, 411 pages. Initially the main content of the thesis is presented. As indicated by the sub-title, the major concern of the author is cultural encounter, i.e. the problem of relationship. As, however, this relationship is illustrated by a wealth of historical sources, the thesis is of considerable interst to students of the history of Danish overseas missions. The subsequent sections of the review deal first with some questions of terminology. Next, a larger section deals with questions concerning the author’s use of non-printed sources. Particularly interesting is the way in which Danish sources are here combined with sources from the British administration and from India itself, among these some hitherto unknown letters written by Mahatma Gandhi. In the following section the author’s mainly negative description of the Danish Missionary Society is critically reviewed. Next, some supplementary remarks are given to the description of the school established by the independent missionary Anne Marie Petersen in Porto Novo. Finally, the key-words »Dependency« and »Identity« are briefly discussed. Although a number of critical observations are included in this review, the concluding statement characterizes the thesis as a well-written, well-documented and competent study.